2018
DOI: 10.1039/c8fo01503a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transglutaminase from Bacillus subtilis and its cross-linking function with a bovine serum albumin model

Abstract: The functional properties of bovine serum albumin were significantly improved by Bacillus subtilis transglutaminase with good thermal and pH stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Finally, NH 4 Cl solution was added to deactivate BTG with a final concentration of 10 mmol L −1 at the end of the reaction time. 23 The sample without BTG-treatment was taken as the control.…”
Section: Solution Preparation and Cross-linking Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, NH 4 Cl solution was added to deactivate BTG with a final concentration of 10 mmol L −1 at the end of the reaction time. 23 The sample without BTG-treatment was taken as the control.…”
Section: Solution Preparation and Cross-linking Reactionmentioning
confidence: 99%
“…25 The optimal temperature (60°C) and pH (8.2) of BTG were obviously different from those of MTG (50°C and pH 6). 23 Simultaneously, the thermostability and pH stability of BTG were superior to MTG. 23 Our previous research demonstrated the successful cross-linking of bovine serum albumin (BSA) and whey protein (WP) by BTG, indicating a dramatic improvement on their functional characteristics.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations